Thu gọn biểu thức sau: (3x-4)^2+2(3x-4)(x-4)+(4-x)^2
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
1) \(\left(x+1\right)\left(x+2\right)-3x\left(x-4\right)=x^2+3x+2-3x^2+12x=-2x^2+15x+2\)
2) \(\left(3x-4\right)\left(x-2\right)=3x\left(x-9\right)\)
\(\Leftrightarrow3x^2-10x+8=3x^2-27x\)
\(\Leftrightarrow17x=-8\Leftrightarrow x=-\dfrac{8}{17}\)
3) \(-3\left(x-4\right)\left(x-2\right)-x^2\left(-3x+18\right)+24x-25\)
\(=-3x^3+6x^2+12x^2-24x+3x^3-18x^2+24x-25=-25\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\left(3x-4\right)^2-2\left(3x-4\right)\left(x-4\right)+\left(x-4\right)^2\)
\(=\left(3x-4-x+4\right)^2\)
\(=4x^2\)
\(\left(3x-4\right)^2+\left(4-x\right)^2-2\left(3x-4\right)\left(x-4\right)=\left(3x-4\right)^2-2\left(3x-4\right)\left(x-4\right)+\left(x-4\right)^2=\left(3x-4-x+4\right)^2=\left(2x\right)^2=4x^2\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) (x2-1)(x2+4)(x2-4)=(x2-1)(x4-16)
b) 9x2+6x+1+4-9x2= 6x+5
![](https://rs.olm.vn/images/avt/0.png?1311)
`@` `\text {Ans}`
`\downarrow`
`a)`
`(3x^2 + 2x)*(x^2 - 3) + (4 - x^3) * (3x+2)`
`= 3x^2(x^2 - 3) + 2x(x^2 - 3) + 4(3x+2) - x^3(3x+2)`
`= 3x^4 - 9x^2 + 2x^3 - 6x + 12x + 8 - 3x^4 - 2x^3`
`= (3x^4 - 3x^4) + (2x^3 - 2x^3) - 9x^2 + (-6x+12x) + 8`
`= -9x^2 + 6x + 8`
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\left(x+2\right)^2-\left(x+4\right)^2+x^2-3x+1\)
\(=x^2+4x+4-x^2-8x-16+x^2-3x+1\)
\(=x^2-7x-11\)
\(\left(x+2\right)^2-\left(x+4\right)^2+x^2-3x+1\)
\(=x^2+4x+4-x^2-8x-16+x^2-3x+1=x^2-7x-11\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a: Ta có: \(x^2-4x\left(3x-4\right)+7x-5\)
\(=x^2-12x^2+16x+7x-5\)
\(=-11x^2+23x-5\)
b: Ta có: \(7x\left(x^2-5\right)-3x^2y\left(xy-6y^2\right)\)
\(=7x^3-35x-3x^3y^2+18x^2y^3\)
c: Ta có: \(\left(5x+4\right)\left(2x-7\right)\)
\(=10x^2-35x+8x-28\)
\(=10x^2-27x-28\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a: \(A=x^2+2+3x^2+2-2x^2-2=2x^2+2\)
b: \(B=2x-3-\left(3x-2\right)-\left(2x-4\right)\)
\(=2x-3-3x+2-2x+4=-3x+3\)
c: \(C=6-3x+3x+10=16\)
d: \(D=\left|3x-8\right|+\left|x+2\right|\)
\(=3x-8+x+2=4x-6\)
\(=\left(3x-4+4-x\right)^2=\left(2x\right)^2=4x^2\)
\(\left(3x-4\right)^2+2\left(3x-4\right)\left(x-4\right)+\left(x-4\right)^2\)
\(=\left(3x-4+x-4\right)^2\)
\(=\left(4x-8\right)^2\)